Cytokine Storm in COVID-19: An Overview, Mechanism, Treatment Strategies, and Stem Cell Therapy Perspective - Azmi, Nuriza Ulul; Puteri, Meidi Utami; Lukmanto, Donny (Pharmaceutical Sciences and Research, 2020)
Coronavirus disease 2019 (COVID-19) is the disease caused by the highly transmittable novel coronavirus (SARS-CoV-2) infections. The disease was found at the end of December 2019, in Wuhan, China, and quickly spread worldwide with a higher mortality rate compared to the previous coronavirus disease. Cytokine plays an important role in the inflammatory response against coronavirus infection. However, in severely ill patients with COVID-19, an excessive amount of cytokine serum level (cytokine storm) has been associated with the aggravation of coronavirus disease leading to acute respiratory distress syndrome (ARDS). Thus, the management of the cytokine storm could be the key to stop COVID-19 progression. This article reviews an overview related to SARS-CoV-2 and COVID-19, mechanism and prospective treatment strategies for cytokine storm in COVID-19, and a viewpoint of stem cells perspective. The purpose is to provide some information that could be useful for future guidelines in the clinical management of COVID-19.